PELATIHAN PEMBUATAN WEB COMPANY PROFILE UNIT KERJA KARANG TARUNA KELURAHAN TEGAL PARANG - Ariani, Fattya; Sumarna, Sumarna; Nurdin, Hafis; Supriadi, Riki (LPPM Universitas Nusa Mandiri, 2024)
Karang Taruna is an organization that exists in Indonesia. Because surely in every village there is this organization. Karang Taruna is a place for teenagers to develop themselves to be responsible and have a social spirit. Technological developments can now be enjoyed by everyone throughout the world. Looking for information, we just have to type in Google what we want, after that so many references appear so that we can read the latest information without fear of missing out on information and this is a very significant difference where in the past it was very difficult to get the latest information and You have to wait a while to get this information. Now a problem where people don't know about Karang Taruna Tegal Parang Village and the activities they carry out. The solution offered is training in creating a company profile website for Karang Taruna, Tegal Parang. The training is carried out using the Technical Assistance method in the form of Training. The results obtained from this training were that the youth organization administrators can understand how to create a company profile website and can host the website they created. So that it can produce the latest information to citizens.